Analisis SWOT pada PT. Aisin Indonesia Automotive - Setiawan, Muhammad Faizal Nur; ., Daspar (CV. ITTC INDONESIA, 2025)
This study aims to analyze the internal and external conditions of PT AISIN Indonesia Automotive using a SWOT approach to formulate appropriate business strategies. The analysis reveals that the company possesses significant strengths, such as technological support from the AISIN Group, production efficiency, and strong relationships with Japanese OEMs. Conversely, the main weaknesses include dependence on the Japanese market and limited local R&D capabilities. Strategic opportunities include the growth of the electric vehicle (EV) market, government incentives, and regional export potential, while threats arise from global competition and economic fluctuations. Based on the IFE (3.49) and EFE (3.44) scores, PT AISIN is positioned in Quadrant I (Grow and Build) of the strategic matrix, indicating that the company is in a strong position to pursue aggressive growth. Recommended strategies include market expansion, strengthening local innovation, digital transformation, and product diversification. This analysis provides a solid foundation for management in designing sustainable strategic policies and decisions.